An empirical study on impulse consumption intention of livestreaming e-commerce: The mediating effect of flow experience and the moderating effect of time pressure - Dong, Wei-wei; Wang, Yong-qiang; Qin, Jian (Frontiers in Psychology, 2023)
Based on the Stimulus-Organism-Response (S-O-R) model, this paper studies the impulsive consumption mechanism of consumers participating in livestreaming e-commerce from the perspectives of information source characteristics and social presence and examines the mediating effect of flow experience and the moderating effect of time pressure. Based on the consumption data of 268 live shoppers, multiple regression analysis and Bootstrap method were used to test the research hypothesis. The empirical results show that the credibility, professionalism, attractiveness, and interactivity of live information sources have significant positive impacts on consumers’ flow experience and impulsive consumption intention. Furthermore, coexistence, communication and emotional presence of social presence have a significant positive impact on consumers’ flow experience and impulsive consumption intention. Flow experience plays part of the mediating role in the process of the characteristics of livestreaming information sources and social presence affecting consumers’ impulsive consumption intention, while time pressure has a positive moderating effect in the relationship between livestreaming information source characteristics and coexistence presence and flow experience. The higher the time pressure, the stronger the promotion of live information source characteristics and coexistence presence on flow experience. This study enriches the research literature on the consumption driving mechanism of livestreaming e-commerce and offers practical enlightenment and reference to improve the effectiveness of livestreaming e-commerce anchors. It is also one of the first studies to apply the theory of flow and social presence to the impulsive consumption intention of livestreaming e-commerce.